A GPR SURVEY FOR WATER EXPLORATION IN A CRYSTALLINE ROCK TERRAIN - Travassos, Jandyr Menezes; Menezes, Paulo de Tarso Luiz (Águas Subterrâneas, 2000)
The vast majority of mineral water occurrences in Brazil are associated to fractures zones in crystalline rocks. Underground water exploration is usually based on geological studies (photo-interpretation) combined with geophysical surveys, mainly electrical methods and VLF. In this paper we demonstrate the use of GPR method in the exploration of underground water in crystalline terrain. An example of data collected at one known spring in the district of Petrópolis is given. Petrópolis is a major producer in the Rio de Janeiro State. The saturated region is clearly outlined in the GPR section as a zone of attenuation and inversion of the wavelet phase polarity.